FeatureIDE: An extensible framework for feature-oriented software development - Thüm, Thomas; Kästner, Christian; Benduhn, Fabian; Meinicke, Jens; Saake, Gunter; Leich, Thomas (Science of computer programming, 2014)
FeatureIDE is an open-source framework for feature-oriented software development (FOSD) based on Eclipse. FOSD is a paradigm for the construction, customization, and synthesis of software systems. Code artifacts are mapped to features, and a customized software system can be generated given a selection of features. The set of software systems that can be generated is called a software product line (SPL). FeatureIDE supports several FOSD implementation techniques such as feature-oriented programming, aspect-oriented programming, delta-oriented programming, and preprocessors. All phases of FOSD are supported in FeatureIDE, namely domain analysis, requirements analysis, domain implementation, and software generation. ► Tool support for programming languages and concepts is crucial. ► Previously, FeatureIDE only integrated feature-oriented programming. ► Now, we integrate aspect-oriented, delta-oriented programming, and preprocessors. ► FeatureIDE is an open-source framework, and it can easily be extended for further languages. ► It is used to create large-scale case studies for various research questions.